Crafting strategy embodied metaphors in practice - Heracleous, Loizos Th (Cambridge University Press, 2011)
The rationalist approach to strategizing emphasizes analytical and convergent thinking. Without denying the importance of this approach, this book argues that strategists must learn to complement it with a more creative approach to strategizing that emphasizes synthetic and divergent ways of thinking. The theoretical underpinnings of this approach include embodied realism, interpretivism, practice theory, theory of play, design thinking, as well as discursive approaches such as metaphorical analysis, narrative analysis, dialogical analysis and hermeneutics. The book includes in-depth discussions of these theories and shows how they can be put into practice by presenting detailed analyses of embodied metaphors built by groups of agents with step-by-step explanations of how this process can be implemented and facilitated. The link between theory and practice is further supported by the inclusion of several vignettes that describe how this approach has been successfully employed in a number of organizations, including BASF and UNICEF.